Stink bugs (Hemiptera: Pentatomidae) from Brazilian Amazon: checklist and new records - Da Silva, Valeria Juliete; Dos Santos, Cleverson Rannieri Meira; Fernandes, Jose Antonio Marin (Zootaxa, 2018)
A list of the stink bugs (Pentatomidae) species of the Brazilian Amazon is provided for the first time, based on literature review and identification of the specimens of Pentatomidae deposited in the entomological collection of the Museu Paraense Emílio Goeldi (MPEG). Amazonian data base presented here has 324 species of Pentatomidae belonging to 102 genera, ten tribes and five subfamilies: Asopinae, Cyrtocorinae, Discocephalinae, Edessinae and Pentatominae. The Pentatominae has the largest number of species registered to Brazilian Amazon (144 species). The MPEG entomological collection has 122 species distributed in 53 genera, nine tribes and five subfamilies. Forty species from eight tribes and four subfamilies are recorded for the first time to Brazilian Amazon, including species from Podisus Herrich-Schäffer (Asopinae); Adoxoplatys Breddin, Macropygium Spinola, Neoadoxoplatys Kormilev, Ochlerus Spinola and Platycarenus Fieber (Discocephalinae); Edessa Fabricius (Edessinae); Arocera Spinola, Arvelius Spinola, Banasa Stål, Dichelops Spinola, Euschistus Dallas, Mormidea Amyot & Serville, Oebalus Stål, Pellaea Stål, Piezodorus Fieber, Proxys Spinola and Thyanta Stål (Pentatominae). Three of these species–Podisus maculiventris (Say, 1831) Neoadoxoplatys saileri Kormilev, 1956 and Edessa laticornis Stål, 1872—are new records to South America. The number of species of Pentatomidae to Brazilian Amazon represents approximately 50% of the species registered to Brazil. Such list of species is important to better understand the distributional range and diversity of the species of Pentatomidae in the Amazon region.